Solid-phase spectrophotometry determination of Нg (II) using hromazurol S - Костенко, Єлизавета Євгеніївна; Бутенко, Олена Миколаївна (Eastern-European Journal of Enterprise Technologies, 2014)
The following optimal interaction conditions of mercury with hromazurol S in the phase of polymeric anion exchanger АV-17´8-С1 are determined: maximum extraction (85%) of Hg (II) is achieved at pH 1 within 20 minutes of phase contact from the volume of 50 cm3. Quantitative sorption is also possible with 500 cm3 of the solution. The concentration factor is 1667 cm3/g. The detection limit is 20 mkg/dm3. Mercury (II) is virtually not adsorbed by anion exchanger AV-17´ 8-C1. Baer's law is fulfilled within the concentration range of mercury (20-100) mkg/dm3 (V=50sm3). lопт = 580 nm. Complexation of Hg (II) with SF HAZ is affected by: 1:1000 - Cu (II), Zn (II), Cd (II), Zr (IV), Fe (III); Pb (II), Co (II), Al (III) l.z.m., Br-, SO42-, F-, NO3-, 1:10 - Sn (ІV). The complexation chemistry in the studied system is considered. Ratio of components in the complex - Hg:HAZ-A=1:1 is defined. Conditional stability constant of complex lgb1 = 8.1 ± 0.7 is calculated. The obtained data were used for developing the new method for SPS determination of mercury in food and environmental objects, which does not yield to the best standard methods in respect of sensitivity, selectivity and expressness, and outstrips them in respect of the experiment simplicity. The method is tested for fungi analysis. Data validation is carried out by the “introduced-found” method. Convergence of the results, obtained using the new and standard (AAS) methods validates them.